Health-related quality of life in type 1 diabetes mellitus pediatric patients and their caregivers in Spain: an observational cross-sectional study. (2nd September 2019) - López-Bastida, Julio; López-Siguero, Juan Pedro; Oliva-Moreno, Juan; Vázquez, Luis Alberto; Aranda-Reneo, Isaac; Reviriego, Jesús; Dilla, Tatiana; Perez-Nieves, Magaly
Abstract: Objectives: This study assessed the health-related quality of life (HRQOL) of pediatric patients with type 1 diabetes mellitus (T1DM) and their caregivers. Methods: CHRYSTAL was an observational cross-sectional study conducted in Spain in 2014 on 275 patients under 18 years old diagnosed with T1DM. Patient/caregiver pairs were stratified by patients' HbA1c level (≥7.5% versus <7.5%) and by presence or absence of T1DM complications and/or comorbidities. EQ-5D and PedsQL questionnaires were administered to patients and caregivers. Results: On the EQ-5D, according to caregivers' perception, 17.7% of children experienced moderate pain or discomfort, 9.7% suffered problems performing usual activities, and 13.2% demonstrated moderate anxiety or depression. Mean EQ-5D index score was 0.95 and mean visual analog scale (VAS) score was 86.1. By HbA1c level (≥7.5% versus <7.5%), mean index scores were 0.94 and 0.95, and mean VAS scores were 82.8 and 89.2, respectively. Mean index scores were 0.91 for children with complications and/or comorbidities and 0.96 for children without. Mean VAS scores were 83.7 and 87.2, respectively. HRQOL per the PedsQL tool ranged from 68.1 (ages 2–4) to 73.1 (ages 13–18). EQ-5D index and VAS scores were significantly correlated (rho = 0.29–0.43) with several age groups of the PedsQL. EQ-5D scales showed significant moderate correlation between EQ-5D-Y and EQ-5D-3L proxy VAS score (rho = 0.45; p < .001). Conclusions : Patients with few complications and controlled HbA1c reported a relatively high HRQOL. The results suggest that parent-proxy EQ-5D ratings are valid for use as part of an overall health outcomes assessment in clinical studies of T1DM in pediatric patients.